Compactness for Sobolev-type trace operators. (June 2019) - Cavaliere, Paola; Mihula, Zdeněk
Abstract: Compactness of arbitrary-order Sobolev type embeddings for traces of n -dimensional functions on lower dimensional subspaces is investigated. Sobolev spaces built upon any rearrangement-invariant norm are allowed. In particular, we characterize compactness of trace embeddings for classical Sobolev, Lorentz–Sobolev and Orlicz–Sobolev type spaces.